2013
DOI: 10.1186/1465-9921-14-38
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transcriptome of native nasal epithelium expressing F508del-CFTR and intersecting data from comparable studies

Abstract: BackgroundMicroarray studies related to cystic fibrosis (CF) airway gene expression have gone some way in clarifying the complex molecular background of CF lung diseases, but have made little progress in defining a robust “molecular signature” associated with mutant CFTR expression. Disparate methodological and statistical analyses complicate comparisons between independent studies of the CF transcriptome, and although each study may be valid in isolation, the conclusions reached differ widely.MethodsWe carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 56 publications
(112 reference statements)
9
77
0
Order By: Relevance
“…Other studies have profiled mRNA expression within the context of CF. At least three studies have profiled mRNA expression in the CF nasal epithelium (Ogilvie et al, 2011, Wright et al, 2006, Clarke et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have profiled mRNA expression within the context of CF. At least three studies have profiled mRNA expression in the CF nasal epithelium (Ogilvie et al, 2011, Wright et al, 2006, Clarke et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between studies may be partly explained by different experimental procedures employed. These differences include genotype of the cells used, statistical or normalisation approaches and tissue type; such as bronchial and nasal brushings (Ogilvie et al, 2011, Wright et al, 2006, Clarke et al, 2013, isogenic bronchial cells (Virella-Lowell et al, 2000), primary tracheal and bronchial cell cultures (Zabner et al, 2005) and foetal tracheal cells (Verhaeghe et al, 2007). It remains to be determined what direct contribution mutant CFTR makes to an altered CF transcriptome, and it is highly likely that other factors such as infection and inflammation are major contributors to this altered expression of both lncRNAs and protein coding transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have shown that the nasal transcriptome and its regulation mirror that of the lower airways (16). Finally, we and others have shown dysfunction in the nasal airway epithelium among subjects with lower airway diseases, including asthma, chronic obstructive pulmonary disease, and cystic fibrosis (16)(17)(18)(19)(20). Based on this finding, we believe that the marriage of minimally invasive nasal airway epithelium sampling with CRC methods would allow unprecedented population-based analysis of airway dysfunction across multiple chronic lung diseases.…”
mentioning
confidence: 96%
“…Pendrin up-regulation is seen in: 1) airway epithelial cultures chronically exposed to cytokines, including IL-4, IL-13, and IL-17A; 2) rodent models of inflammatory lung disease, including allergen (ovalbumin)-induced asthma, chronic obstructive pulmonary disease, infection, and industrial toxin exposure; and 3) humans with rhinovirus infection, asthma, cystic fibrosis (CF), rhinitis, and chronic rhinosinusitis (10,11,(17)(18)(19)(20)(21)(22)(23)(24)(25). Pendrin knockout is also associated with reduced lung inflammation in a murine model of Bordetella pertussis lung infection (26).…”
mentioning
confidence: 99%
“…Although pendrin activity and increased ASL hydration were seen only in cell cultures after IL-13 treatment, we note that asthmalike symptoms (cough, wheezing, airway hyperresponsiveness) and increased IL-13 are prevalent in subjects with CF (29), and that IL-13 is common to several airway diseases. Further, alternative CF-relevant inflammatory pathways also increase pendrin expression in freshly isolated airway epithelial cells from CF subjects (23). There is considerable interest in identifying ion transport modulators to increase ASL depth in CF, with ENaC inhibitors and activators of CaCC under development (47).…”
mentioning
confidence: 99%